One step electro-oxidative preparation of graphene quantum dots from wood charcoal as a peroxidase mimetic - Nirala N.R.; Khandelwal G.; Kumar B.; Vinita; Prakash R.; Kumar V. (My University, 2025)
In present study, we highlight one-step electrochemical synthesis of nearly uniform size (~ 5 nm) of graphene quantum dots (E-GQDs) from wood charcoal and their further application as a peroxidase enzyme mimetic. The structural and optical properties of as-synthesized E-GQDs were probed by TEM, AFM, and spectroscopic techniques. Peroxidase enzyme mimetic potential of E-GQDs were examined for colorimetric detection of H2O2 and glucose. E-GQDs allowed a rapid and sensitive detection of glucose with a detection limit of 0.006 mM for dynamic response range of 0.01–0.6 mM. The calculated higher value of Vmax (7.2 × 10−7 M s−1) along with lower Km (0.012 mM) corroborate enhanced the peroxidase-like activity of E-GQDs. Study introduces a cheap and widely available raw material for the electrochemical synthesis of graphene quantum dots with commendable enzyme mimetic activity which may have a huge impact in developing calorimetric bioanalysis systems. © 2017 Elsevier B.V.